Greening aid? understanding the environmental impact of development assistance - Hicks, Robert L. (Oxford : Oxford University Press, 2008)
For over three decades, the impact of aid on the global environment has been the subject of vigorous protest and debate. With billions spent on environmental aid each year, this text seeks to understand why aid is given, how effective it is, and whether aid is actually going to the places with the greatest need.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Economic development -- Environmental aspects; Economic assistance